Evaluation of Processing Time in Primary Sawmilling of Scots Pine (Pinus sylvestris) Logs on a Vertical Band Saw - Stamenkoska, Ana-marija; Temelkova, Anastasija; Zlateski, Goran; Trposki, Zoran; Rabadziski, Branko; Koljozov, Vladimir (Department of Wood Technology, Faculty of Forestry and Wood Tehnology, University of Zagreb, Croatia, 2025)
The efficiency of primary wood processing largely depends on the optimal utilization of macines and tools. Beyond the rational use of sawlogs in sawmilling, the profitability and effective operation of sawmill capacities critically rely on the efficient application of primary processing machines. These machines are primarily tasked with transforming logs into semi-finished products, through which logs are converted into sawn timber through the sawing process. Among the most implemented machines for primary processing are band saws. These types of primary machines allow individual log sawing, where each log is processed separately according to its dimensions and quality class. In such operations, determining the technological capacity is essential, defined as the volume of logs a machine can process within a given timeframe. A key factor affecting technological capacity is the processing time per log, which represents the cumulative duration of all sawing operations and factors involved in sawing , such as log rotation, number of cuts, log length and other related activities. The processing time can be divided into components dependent on the machine’s technological parameters and those influenced by the organization of production within the sawmill. This study presents a detailed analysis of processing times for Scots pine (Pinus sylvestris) sawlogs using a vertical band saw.
Keywords: band saw, primary processing, processing time, sawlogs, Scots pine, technological capacity